Judicial decisions in the Ancient Near East - Démare-Lafont, Sophie; Fleming, Daniel E.; Charpin, Dominique (Writings from the ancient world, 2023)
"This volume presents the first broadly inclusive collection, with accessible text and English translation, of documents related to judicial decisions in the ancient Near East, the oldest setting for such writing in the world. The texts in this volume belong to various genres, especially legal records and letters, and they span almost two thousand years. With such varied material, the work depends on the expertise of specialists in each setting, from the Sumerian of early Ur to the late Akkadian of Babylonia under the Persians. Each chapter includes introductions that place the legal documents in their historical and social context, texts, translations, and commentary. This volume brings the beginnings of law to students and scholars across disciplines"--